Using an Integrated Approach QFD, FAHP and VIKOR to Select an Appropriate ERP System - kamran feizi; Mohammad Sabet motlagh; Mehdi Abedini naeini (مطالعات مدیریت کسب و کار هوشمند, 2015)
Enterprise resource planning systems (ERP) for facilitating the operation of organizations and integration of the process of business data are an important competitive advantage for organizations. To the successful implementation of an ERP system is essential to choose a system that can be aligned with the needs of the organization. Therefore, a proper decision-making approach for the selection of an ERP system is required so that take into accounts the needs and characteristics of the ERP system and also the interaction between them. So in this study, an integrated decision-making framework for the selection of ERP systems based on the concept of QFD, fuzzy analytic hierarchy process and Vikor provided. The framework makes the needs of the organization and also features of ERP system. To validate the model, the model is applied in a case. The results of this study show that among of the criteria, the cost and system performance criteria are the most important and sixth supplier is the most proper supplier. Keywords: Enterprise resource planning (ERP), Quality Function Deployment (QFD), Fuzzy Analytic Hierarchy Process, Vikor Method